Cell lines containing varicella-zoster virus open reading frame 62 and expressing the "IE" 175 protein complement ICP4 mutants of herpes simplex virus type 1. - Felser, J M (1988)
Vero cells were cotransfected with pSV2neo and a recombinant plasmid containing the varicella-zoster virus (VZV) open reading frame 62 (ORF62). Three neomycin-resistant cell lines were isolated and shown to complement two different ICP4 mutants (tsB21 and d120) of herpes simplex virus (HSV) type 1 (HSV-1). VZV-specific RNA could not be detected in these cell lines, but following infection with tsB21, a 4.3-kilobase VZV transcript was detected. This RNA increased in quantity when cells were infected in the presence of cycloheximide. A VZV-specific protein of 175 kilodaltons was detected in extracts of all three cell lines following infection with wild-type HSV-1 but not in uninfected cells. That VZV RNA and protein were detected only in HSV-1 infected cells suggests that a component of the HSV virion activates the expression of VZV ORF62. The increase in RNA expression seen in the presence of cycloheximide indicates that the protein encoded by VZV ORF62, "IE"175, may be autoregulatory. These data provide further evidence that VZV "IE"175 is the functional analog of the HSV ICP4.